(untitled) (Journal of the College of Basic Education, 2025)
This research topic includes a study of the Ottoman military forces in the eighteenth century, their most important formations, and the administrative divisions of the forces from the beginning of Ottoman control over Baghdad in 1534 until the end of Mamluk rule in the eighteenth century. In preparing the research, I relied on sources specializing in the history of the Ottoman Empire and the modern history of Iraq. Because the Ottoman Empire divided Iraq into several provinces, Baghdad was certainly the most important due to its strategic location. Governors were appointed over them, and among their responsibilities was overseeing security and military order in all its forms. However, when the Mamluks assumed power in Baghdad, several changes occurred, which are explained in detail in the research pages regarding the formations and types of the army in the eighteenth century.